Metode Pembelajaran Ramah Remaja di GMIT Jemaat Kalvari Maumere - Djami Bale, Sara Utami; Hattu, Justitia Vox Dei (Didache: Journal of Christian Education, 2023)
Learning methods for teenagers in the church are often equated with learning methods for children. If it is differentiated, it is a kind of modification of the teaching model of children. The teachers are not treating teenagers according to their abilities and needs. Based on the context of the teenagers at GMIT Kalvari, Maumere, this research wants to reveal the extent to which the learning methods used so far are friendly or unfriendly to the teenager group of Generation Z. The research method used is qualitative research using structured interviews to the groups of teacher and teenager and review on the teaching material document "Derap Remaja" that is used in 2022. By using the theory of learning models of Sara Little and generation theory of Gen Z foranalyze the context, results show that teenager-friendly learning is an urgent need because one-way teaching patterns are still strong enough to dominate the teenager learning model at GMIT Kalvari. Therefore, this paper proposes three principles and practical aspects related to the teenager learning methods, which are responsive and dialogical methods that go beyond the monologue one, the active involvement of teenagers in the learning process, and learning process that encourage the teenager to do something in their real life